Is the risk of low birth weight or preterm labor greater when maternal stress is experienced during pregnancy? A systematic review and meta-analysis of cohort studies - Lima, Silvana Andréa Molina [UNESP]; El Dib, Regina Paolucci [UNESP]; Rodrigues, Meline Rossetto Kron [UNESP]; Ferraz, Guilherme Augusto Rago [UNESP]; Molina, Ana Claudia; Neto, Carlos Alberto Pilan; De Lima, Marcelo Aparecido Ferraz [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Public Library of Science (PLoS), 2018)
Antenatal stress is linked to fetal risks that increase the chances of neonatal complications and reduction of child cognitive ability. Therefore, we aimed to evaluate if maternal stress affects fetal, neonatal or child development. The following databases were searched: MED-LINE (1966 to May 2016), Embase (1980 to May 2016), LILACS (1982 to May 2016) and CENTRAL (1972 to May 2016). Observational studies published in English and Portuguese were included whether there was any relationship between fetal and neonatal outcome, such as birth weight, preterm labor, child development with pregnant women that were subjected to any stress type during at least one month of follow-up. Two independent reviewers screened eligible articles, extracted data and assessed the risk of bias. Thus, 8 cohort studies with about 8,271 pregnant women and 1,081,151 children proved eligible. Results suggested a significant association between antenatal stress exposure and increasing rates of low birth weight (Odds ratio (OR) 1.68 [95% Confidential Interval (CI) 1.19, 2.38]). However, there was no statistically significance difference between non-exposed and exposed groups related to preterm labor (OR 1.98 [95% CI 0.91 to 4.31]; I2 = 68%, p = 0.04). Although, results were inconsistent with primary analysis suggesting a significant association between antenatal stress exposure and the occurrence of higher rates of preterm birth (OR 1.42 [95% CI 1.05 to 1.91]; I2 = 68%, p = 0.04) in the sensitivity analysis. Furthermore, the current review has suggested that stress perceived during antenatal negatively influences fetal life and child development. Yet, further studies are necessary with adequate sample size and longer follow-up time to confirm our findings.